Centrally Prepared Cytotoxic Drugs: What Is the Purpose of Their Quality Control? - Lagarce Frederic (De Gruyter, 2017)
To assess the quality of centrally prepared cytotoxics a global approach is being implemented by pharmacists. A risk analysis is performed, and then many in-process controls are proposed. The aseptic process and the material are also fully validated. Moreover the skills of pharmacy technicians are being checked and monitored over time. This short opinion paper discusses the place of in-process quality control within the quality system applied to cytotoxic preparations. It also discusses the pros and cons of analytical control of the final product versus continuous control of each preparation step by eye witness or an electronic device such as a camcorder. Finally the relevancy of controls is discussed in function of different cases and of the human and material resources available in the pharmaceutical technology cytotoxic unit.